Representasi Keperempuanan dan Sistem Patriarki dalam Novel Tarian Bumi Karya Oka Rusmini - Zahratul Umniyyah; Yanuaresti Kusuma Wardhani; Nurhadianty Rahayu (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Representations of womanhood and patriarchy are presented in the novel Tarian Bumi by Oka Rusmini. Stuart Hall's representation theory is used as a theoretical framework. This research explores female figures who experience gender injustice and how patriarchal domination is deeply rooted in Balinese society. By analyzing the female characters, this article finds that women in Tarian Bumi often face various forms of gender injustice. Women experience limited freedom and life choices, derogatory judgments based on caste and physical appearance, and the burden of traditional gender roles that require them to sacrifice personal well-being to meet social expectations. Rigid social norms and sanctions for breaking norms strengthen patriarchal domination, making women who try to violate these norms get severe social sanctions. This article reveals how the novel provides an overview of social realities experienced by Balinese women, criticizing and challenging unfair patriarchal norms. Tarian Bumi exposes oppressive social structures and fights for gender justice in society. This article contributes to discussions about gender representation in literature and the importance of literature as a tool for social change. Keywords: patriarchy, representation, womanhood